2007
DOI: 10.1111/j.1365-313x.2006.02998.x
|View full text |Cite
|
Sign up to set email alerts
|

The fluorouridine insensitive 1 (fur1) mutant is defective in equilibrative nucleoside transporter 3 (ENT3), and thus represents an important pyrimidine nucleoside uptake system in Arabidopsis thaliana

Abstract: SummaryThe fluorouridine insensitive 1 (fur1) locus in Arabidopsis thaliana (L.) Heynh. has previously been identified in a screen for growth resistance towards the toxic compound fluorouridine. Mutation of this locus by ethylmethane sulfonate (EMS) allows mutants to grow on this uridine analogue. We identified that the A. thaliana equilibrative nucleoside transporter (AtENT3) was encoded by the fur1 locus. T-DNA insertional mutant plants for AtENT3 resemble the fur1 mutant phenotype: i.e. they grow on fluorou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(61 citation statements)
references
References 29 publications
2
57
0
2
Order By: Relevance
“…Flö rchinger, S. Hach, B. Jung, M. Traub, R. Wartenberg, C. Salzig, P. Lang, and T. Mö hlmann, unpublished results). ENT3-deficient plants show resistance toward fluorouridine as observed for URH1 overexpressor mutants (Traub et al, 2007). Possibly both enzymes are functionally integrated.…”
Section: Altered Nucleosidase Activity Effects Uridine Degradation Nmentioning
confidence: 86%
See 2 more Smart Citations
“…Flö rchinger, S. Hach, B. Jung, M. Traub, R. Wartenberg, C. Salzig, P. Lang, and T. Mö hlmann, unpublished results). ENT3-deficient plants show resistance toward fluorouridine as observed for URH1 overexpressor mutants (Traub et al, 2007). Possibly both enzymes are functionally integrated.…”
Section: Altered Nucleosidase Activity Effects Uridine Degradation Nmentioning
confidence: 86%
“…The measured maximal activities for UK and UPRT were unchanged in the mutants generated in the course of this work (see Supplemental Figure 2 online). It has to be mentioned that the activities for both enzymes are severalfold in excess compared with uptake rates of uridine (Wormit et al, 2004;Traub et al, 2007). However, it cannot be excluded that the cosubstrate of UPRT phosphoribosyl pyrophosphate limits uracil salvage as mutants in phosphoribosyl pyrophosphate synthesis showed that this metabolite may colimit growth rates in Arabidopsis (Koslowsky et al, 2008).…”
Section: Altered Nucleosidase Activity Effects Uridine Degradation Nmentioning
confidence: 99%
See 1 more Smart Citation
“…Members from four plant species have been characterized at the biochemical level to date – AtENT1, 3, 4, 6, and 7 from Arabidopsis , OsENT2 from rice, HvENT1 from barley and StENT1 and 3 from potato (Table 1). In contrast to mammalian homologs which mediate an equilibrative transport of substrates along a concentration gradient, most plant ENT proteins function as substrate-proton symporters (Li et al, 2003; Wormit et al, 2004; Hirose et al, 2005; Traub et al, 2007). The only known exception so far represents AtENT7 which was shown to catalyze a nucleoside transport in yeast that was hardly affected by the protonophore carbonyl cyanide m-chlorophenyl hydrazone (CCCP) and the pH value of the medium (Wormit et al, 2004).…”
Section: The Equilibrative Nucleoside Transporter Familymentioning
confidence: 99%
“…An AtENT3 mutant was identified as FUR1 and contains a point mutation in the AtENT3 gene which leads to an exchange of glycine to arginine at position 281 and to the loss of function (Wu and King, 1994; Traub et al, 2007). FUR1 mutants and AtENT3 T-DNA mutants are completely resistant against the toxic pyrimidine nucleoside analog 5-fluorouridine (5-FU).…”
Section: The Equilibrative Nucleoside Transporter Familymentioning
confidence: 99%